Renewal Of The Human Rights Court Mechanism To Handle Serious Violations Resulting From Contemporary Conflicts - Ansari, Muhammad (Green Publisher Indonesia, 2025)
Horizontal and vertical conflicts that have occurred in Indonesia in recent decades have given birth to various forms of gross human rights violations, such as mass killings, torture, and enforced disappearances. However, the existing human rights justice mechanism has not been able to provide substantive justice and legal certainty for victims. Structural and procedural weaknesses in the judicial system, as well as the limited authority of investigative agencies, are the main inhibiting factors in the resolution of these cases. This study aims to evaluate the effectiveness of the applicable human rights justice mechanisms and offer a systemic form of legal reform. The method used is juridical-normative with a legislative and conceptual approach. Data was collected through a literature study of primary and secondary legal sources. The results of the study show the urgency of comprehensive reform in the human rights justice system to ensure accountability of perpetrators, recovery for victims, and prevention of future violations.